Analysis of Hospital Management Information System Implementation Using Modification of Integrated Model and Its Implication on the Quality of Electronic Medical Records - Rasipin, Rasipin; Munawar, Munawar; Arrozi, Muhammad Fachrudin; Kusumapradja, Rokiah; Pamungkas, Rian Adi; Nofierni, Nofierni (Poltekita : Jurnal Ilmu Kesehatan, 2024)
The implementation of electronic medical records through the Hospital Management Information System Generic Open Source (SIMRS-GOS) Version-2 (V2) developed by Indonesian Ministry of Health has been implemented since 2012. The data shows that the failure rate in using information systems in developing countries is quite high due to the quality and reliability of the system, people and support from the organization. The aim of this research is to analyze the implementation of SIMRS-GOS at three interrelated levels namely human-technological-organizational factors and their benefits on the quality of electronic medical records. The research design uses a quantitative exploration. The research subjects consist of doctors, nurses and midwives, totaling 235 respondents. The data is obtained through a questionnaire. Statistics analysis uses structural equation modeling. The research results show that there is a significant positive influence among human factors, organizational factors and user satisfaction on behavior intentions; use behavior towards net benefits; net benefits and technology factors on user satisfaction; technological factors and net benefits on behavior intentions through user satisfaction; use behavior towards user satisfaction through net benefits. There is a very strong significant correlation among the three human-technology-organization factors and finally there is a significant influence of net benefits on the quality of electronic medical records. Based on these results, it is concluded that the implementation of SIMRS-GOS is acceptable to users at Brebes District Public Hospital. It is also considered successful and has implications for the quality of electronic medical records.